Formation Of Conflict Logical Competence of An Educational Institution Leader: Modern Challenges and Ways to Overcome Them (Journal of Pedagogical Inventions and Practices, 2026)
The relevance of the present study is determined by several factors’ characteristic of contemporary educational practice. Research findings indicate that a considerable proportion of conflicts in educational institutions are associated with insufficient managerial competence and ineffective communication processes